Grammar in Language Teaching The Missing Balance - El-Hemri, Naji (مجلة كلية الاداب, 2022)
The teaching of grammar is a basic element in any language teaching/learning process world-wide. This article addresses the question of how much grammar we need and, in some extreme cases, whether we need to teach grammar at all. The article concentrates in its early part on the proper definition of grammar and how it is to be conceived. Then a move is made to present the two controversial issues of how much or how little grammar we need to teach as well as the role that grammar can play in any communicative act. The writer does not take any specific stance, for or against the teaching of grammar. Instead a brief review is presented highlighting the views of people who are authorities in the field to reflect their ideas and believes on issues regarding grammarfull and grammarless teaching. The above-mentioned views reflected a general agreement, though to different extents, on the importance of grammar and they also showed a general inclination towards striking a balance between the two trends of grammarfull and grammarless teaching. Consequently, a brief part of the article is given to highlighting the importance of such balance. Due to interest and concerns for which there is neither the place nor the time to be addressed in this article, it was almost impossible for the writer to discuss such an issue without shading some light on the Libyan situation. Consequently, the article ends with a very brief idea on the teaching of grammar in the Libyan context.